Herbal recommendations for treatment of COVID-19 symptoms according to Persian medicine - Hoorieh Mohammadi Kenari; Bahare Sadat Yousefsani; Fatemeh Eghbalian; Ali Ghobadi; Amirhosein Jamshidi; Somaye Mahroozade (Institue of Medicinal Plants, ACECR, 2021)
Background: The outbreak of COVID-19 has spread quickly all over the world. Apparently, the uncontrolled increases in the inflammatory and the immune processes are its major pathologies. Therefore, the use of natural plants containing antioxidant factors for the regulation of the immune system can be useful for the inflicted patients. Many epidemic diseases have occurred throughout human history. Persian physicians such as Avicenna offered solutions to these epidemics that were helpful in controlling these diseases. Objective: In this study, we introduce the herbs according to traditional Persian medicine's point of view that confirm their having antitussive, antipyretic, anti-viral, anti-inflammatory and antioxidant effects. Methods: In this regard, a thorough search was done on the detoxifier and immuno-modulatory plants in the Persian medicine books such as Makhzan-ol Advieh" and "Tohfat ol momenin" and "Qanun fi al tib". Then, the herbs that were effective in fever and pulmonary diseases were browsed and arranged, and their pharmacological properties were also searched in the scientific databases. Results: This study examined the antipyretic, antitussive and immune-enhancing properties of the plants cited in Persian medicine books and showed that plants such as orange, sweat lemon, citron, myrtle and lavender have antipyretic, antitussive, anti-inflammatory, antioxidant and antimicrobial properties. Conclusion: It seems that the introduced plants could be potential candidates for animal studies and clinical trials. However, more studies are needed to prove their specific effectiveness.